2015
DOI: 10.1111/dom.12494
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin as adjunct to insulin in patients with type 1 diabetes: a 4‐week, randomized, placebo‐controlled trial (EASE‐1)

Abstract: AimsTo investigate the pharmacodynamics, efficacy and safety of empagliflozin as adjunct to insulin in patients with type 1 diabetes.MethodsA total of 75 patients with glycated haemoglobin (HbA1c) concentrations of ≥7.5 to ≤10.5% (≥58 to ≤91 mmol/mol) were randomized to receive once‐daily empagliflozin 2.5 mg, empagliflozin 10 mg, empagliflozin 25 mg, or placebo as adjunct to insulin for 28 days. Insulin dose was to be kept as stable as possible for 7 days then adjusted, at the investigator's discretion, to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
165
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(187 citation statements)
references
References 28 publications
14
165
0
4
Order By: Relevance
“…The mechanism by which SGLT2 inhibition raises LDL-C levels remains unclear. It has been suggested that the increase in LDL-C may be partly due to hemoconcentration, as SGLT2 inhibitors induce volume contraction subsequent to increased urinary volume (4,5). However, the transient diuretic effect of SGLT2 inhibitors may not completely contribute to the observed LDL-C increase.…”
mentioning
confidence: 99%
“…The mechanism by which SGLT2 inhibition raises LDL-C levels remains unclear. It has been suggested that the increase in LDL-C may be partly due to hemoconcentration, as SGLT2 inhibitors induce volume contraction subsequent to increased urinary volume (4,5). However, the transient diuretic effect of SGLT2 inhibitors may not completely contribute to the observed LDL-C increase.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] Use of SGLT2 inhibitors was associated with improvements in average glucose control, reduced postprandial hyperglycemia and glycemic variability, reduced body weight, and reduced insulin dose requirements. [11][12][13] Dual SGLT1/2 inhibitor, sotagliflozin, has also demonstrated significant reductions in HbA1c, postprandial glucose, weight, and insulin doses.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of symptomatic hypoglycemia or hypoglycemia requiring assistance was not increased. 17 The 24-hour mean glucose area under curve was significantly reduced, compared to placebo: adjusted mean difference was -30.2 mg/dl/h (95% confidence interval [CI] -42.2 to -18.2) with empagliflozin 10 mg and -33.0 mg/dl/h (95% CI -44.8 to -21.1) with empagliflozin 25 mg. Glucose variability was significantly decreased, time spent in target glucose range was increased and there was no increase in time spent in hypoglycemia. 18 In an 18-week, phase 2 study including 351 patients on multiple daily injections or CSII, canagliflozin was associated with decreases in HbA1c, insulin dose and body weight.…”
Section: Clinical Evidence With Sodium-glucose Co-transporter-2 Inhibmentioning
confidence: 97%
“…The prevalence of overweight and obesity among newly diagnosed T1D subjects was 21-22% in the [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] year age group in the Pediatric Diabetes Consortium and the SEARCH for Diabetes in Youth study. 1,2 This has been attributed to a general worldwide increase in prevalence of obesity and similar risk factors such as family history, ethnicity, and sedentary lifestyle may be contributory.…”
mentioning
confidence: 99%